Students Perception on Utilizing Pair Work in Writing Descriptive Text at SMPN 7 Padang - Yulsa, Fadli Muhamad; Fatimah, Sitti (Universitas Syiah Kuala, 2025)
This study aims to investigate students perceptions of utilizing pair work in writing descriptive paragraphs at SMPN 7 Padang. Writing descriptive texts is a complex skill that requires mastery of vocabulary, grammar, organization, and creativity, which often poses challenges for English as a Foreign Language (EFL) learners. Pair work has been proposed as an effective strategy to enhance engagement and support the writing process through collaboration and peer interaction. This quantitative descriptive research involved 32 eighth-grade students selected through total sampling. Data was collected using a validated questionnaire consisting of 20 items on a four-point Likert scale, covering four indicators: attractiveness, effectiveness, relevance, and perceived motivation. The results indicated that students perceptions were generally positive, with attractiveness scoring the highest mean (3.15), followed by perceived motivation (3.08), relevance (2.99), and effectiveness (2.97). Findings suggest pair work increases enjoyment, facilitates task completion, and supports long-term writing development, although challenges remain regarding equal contribution and confidence building. It is recommended that teachers implement structured work activities, promote fair participation, and integrate reflective follow-up tasks to maximize their benefits in writing instruction